Reproductive potentials, meat yield and egg quality characteristics of indigenous dwarf chicken of Bangladesh - Md Ferdaus, Abu Jafur; Bhuiyan, Mohammad Shamsul Alam; Bhuiyan, AK Fazlul Haque; Ali, Md Shawkat; Hassin, Begum Mansura; Howlider, Md Abdur Rahman (Asian Journal of Medical and Biological Research, 2016)
The study was conducted to investigate reproductive potentialities, meat yield and egg quality characteristics of indigenous dwarf chicken (IDC) of Bangladesh under intensive management condition. The experiment was conducted at BAU Poultry farm for a period of 26 months from March 2013 to April 2015.A total of 499 eggs were incubated to examine hatching performance, 64 eggs were used to determine egg quality characteristics and 33 birds of 24 weeks age were slaughtered to investigate meat yield characteristics. The mean of hatching egg weight and IDC chick weight were 39.81g and 26.68g, respectively. Estimated chick weight was 67.19% of the egg weight. The average mature body weight and age at sexual maturity of IDC was 1093.20 g and 166.53 d, respectively. The average hen day egg production of IDC up to 32 and 75 weeks of age was 55.22 and 37.43%, respectively. The estimated fertility and hatchability of IDC eggs were 78.36 and 71.80%. Among the meat yield parameters considered, dressed weight, breast weight and thigh meat weight varied significantly (P<0.05) between the males from IDC and the chicken with normal size shank (CNS). IDC also differed significantly (P<0.01) from CNS in terms of neck length (P<0.01) and drumstick bone length. Egg quality parameters like egg weight, shape index, yolk diameter and egg breaking strength varied significantly (P<0.05) between IDC and CNS. In addition, eggs of IDC and CNS showed significant (P<0.01) variation in dry albumen weight and albumen dry matter percent. In conclusion, the findings of the present study provided with some basic information about the potentialities of IDC which could be utilized in future breeding program. Asian J. Med. Biol. Res. December 2015, 1(3): 416-423